SLOVENIAN FOLKTALE THE GIRL AND THE POT (MOJCA POKRAJCULJA, ATU 283C*) AND LITERARY TALES (Philological Studies, 2019)
Vinko  Moderndorfer  (1894-1958)  firstly  published  the Carinthian  folk  tale  Mojca Pokrajculja in 1924 in the collection National Tales from Mežica Valley. In the next (extended) editions of the Carinthian Folk Tales (1937, 1946, 1957 and 1972) he published similar tales Deklica veka [The Girl is Crying]  and Mojca Pokrajculja. Although both well-known, the place in the Slovenian Primary School Curriculum  for 1  grade (2011)  has text  Mojca Pokrajculja , which is also better known. On the basis of the international classification (Uther  2004, 2011) Monika Kropej (2012, 2015)  suggested for this tale classification under the number ATU 283C*. The basic type  can include the motifs of folktale types  ATU 15 (The Theft of Food by Playing Godfather ), ATU 283B* (The House of the Fly) and  ATU 480A (Girl and Devil in a Strange House),  and even the type ATU 123 (The Wolf and the Kids) or ATU 333 (Little Red Riding Hood). In literarure can be find intertextual reminiscences (Juvan 2000) with the Grimm folktale Wedding of Mrs Fox (KHM 38, ATU 65 The She-Fax's Suitors). Due to intertextuality Mojca Pokrajculja can be classified also as Formula Tale or  Chain Tale, based on the sequence of animals (chains based of numbers, objects, animals, names, death, eating and other events).
Keywords: The Girl and the Pot, Mojca Pokrajculja, The Types of Slovenian folktales, animal tales